Analisis Perbedaan Efektivitas Dan Efisiensi Anggaran Pendapatan Dan Belanja Daerah (APBD) Pada Covid-19instansi Pemerintah Sumatera Barat Di Masa Sebelum Dan Saat Pandemi ( Studi Pada Ringkasan APBD Kabupaten/Kota Sesumatera Barat Periode 2017-2020 ) - Indrayeni (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This study aims to analyze the difference in effectiveness and efficiency of regional revenue and spending budgets (APBD) in west Sumatra government agencies in the period before and during the covid-19 pandemic (study on summary apbd district / city in West Sumatra period 2017-2020). The population in this study is all districts / cities in West Sumatra in 2017 to 2020. The number of samples in this study is 19 districts / cities in West Sumatra.The data analysis technique used is multiple regression analysis with SPSS version 23. The data used in this study is secondary data. The results of the analysis showed that there was no difference in the level of effectiveness in the revenue and spending budgets of West Sumatra province before and during the Covid-19 pandemic and there was no difference in the level of efficiency ratio in the revenue and spending budgets of West Sumatra province before and during the Covid-19 pandemic.